Teología y dominación: la biografía de San Antonio de Atanasio y la regulación del deseo - Pimentel Chacón, Jonathan (2008)
This article presents and discusses the motives for and forms of the regulation of desire in latin monastic christianity. It concentrates its discussion on The Biography of Saint Anthony written by Athanasius and it affirms the foundational character of this text to understand the renouncement of body and desire in the history of chrisitianity.